Interaction of Immobilised Unfractionated and LMW Heparins with Proteins in Whole Human Plasma - Zammit, Adrian; Pepper, Duncan S; Dawes, Joan (Thrombosis and Haemostasis, 1993)
The profile of proteins bound to immobilised heparins in hirudin-anticoagulated human plasma was analysed. In molar terms, antithrombin III was the most abundant protein bound to therapeutic doses of unfractionated heparin (Mr = 12,000), whereas heparin cofactor II constituted <1% of the protein bound. Histidine-rich glycoprotein was the only plasma protein likely to influence anticoagulant activity by direct competition with antithrombin III, though significant quantities of complement Factor H, fibrinogen, fibronectin, vitronectin and apolipo-protein B were also detected. Only traces of von Willebrand factor, complement factor I, inter-α-trypsin inhibitor, a2-macro-globulin, serum amyloid P and transferrin were identified, and neither thrombospondin nor platelet factor 4 were measurable. Binding of both antithrombin III and histidine-rich glycoprotein varied with the ratio of heparin to plasma. Clexane (Mr = 4,500) also bound anti thrombin III, but both histidine-rich glycoprotein and vitronectin were quantitatively significant neutralising proteins. Neutralising proteins dominated the binding profile for Oligo H (Mr = 2,200).